Early initiation of direct anticoagulation after stroke in patients with atrial fibrillation. (12th July 2020) - D'Anna, L.; Filippidis, F. T.; Antony, S.; Brown, Z.; Wyatt, H.; Malik, A.; Sivakumaran, P.; Harvey, K.; Marinescu, M.; Bentley, P.; Korompoki, E.; Veltkamp, R.
Abstract : Background and purpose: The safety of early initiation of anticoagulant therapy in patients with ischaemic stroke related to atrial fibrillation (AF) is unknown. We investigated the safety of early initiation of direct oral anticoagulants (DOACs), vitamin K antagonists (VKAs) or no anticoagulation. Methods: This observational, retrospective, single‐centre study included consecutive patients with recent (<4 weeks) ischaemic stroke and AF. The primary outcome was the rate of major (intracranial and extracranial) bleeding in patients on different treatment schemes, i.e. DOACs, VKAs and not anticoagulated. We also investigated the rate of ischaemic cerebrovascular events and mortality. Results: We included 959 consecutive patients with AF and ischaemic stroke followed up for an average of 16.1 days after the index event. A total of 559 out of 959 patients (58.3%) were anticoagulated with either VKAs ( n = 259) or DOACs ( n = 300). Anticoagulation was started after a mean of 7 ± 9.4 days in the DOAC group and 11.9 ± 19.7 days in the VKA group. Early initiation of any anticoagulant was not associated with an increased risk of any major bleeding [odds ratio (OR), 0.49; 95% confidence intervals (CI), 0.21–1.16] and in particular of intracranial bleeding (OR, 0.47; 95% CI, 0.17–1.29; P = 0.143) compared with no anticoagulation. In contrast to VKAs (OR, 0.78; 95% CI, 0.28–2.13), treatment with DOACs (OR, 0.32; 95% CI, 0.10–0.96) reduced the rate of major bleeding compared with no anticoagulation. Early recurrences of ischaemic stroke did not differ significantly among the three groups. Conclusions: Starting DOACs within a mean of 7 days after stroke appeared to be safe. Randomized controlled studies are needed to establish the added efficacy of starting anticoagulation early after stroke.